PENETAPAN STATUS TERSANGKA PENGGUNA NARKOTIKA BERDASARKAN HASIL TES URINE - HOTMAIDA SIMANJUNTAK (LP2MTBM MAKARIOZ, 2020)
The results of urine tests through a forensic laboratory examination are types of evidence not mentioned in Article 184 of the Criminal Procedure Code, but the assessment is the same as visum et repertum, it is the result of expert knowledge on the basis of oath of office as outlined in the form of a letter. So that urine test results can be used as evidence to determine a person becomes a suspect in a narcotic crime in addition to other evidence.The problem in this research is how the Legal Arrangement of Narcotics Abuse, How the Position of Urine Test Results as Evidence in Determining the Status of Suspected Narcotics Users by BNN, What are the Obstacles of BNN in North Sumatra Province in Eradicating Narcotics Abuse. The research method used is through the Normative Juridical approach, this research is normative empirical.The results showed that the Narcotics misuse act was an extraordinary crime and was classified as a special criminal act regulated in a special law namely Law Number 35 Year 2009 concerning Narcotics, in accordance with the Criminal Procedure Code that to establish a person as the suspect has a minimum of 2 pieces of evidence, then the National Narcotics Agency which has the authority to conduct an investigation and investigation can use the results of a urine test as one of the legal pieces of evidence. Urine test results can be used as evidence of letters and expert statements because the urine test is carried out by experts in forensic laboratories that are made in writing. Constraints experienced by North Sumatra's National Narcotics Agency in eradicating narcotics crime include the lack of budget, the lack of human resources both in quantity and competence and the lack of facilities and infrastructure owned.